2015
DOI: 10.1111/sltb.12161
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors, Warning Signs, and Drivers of Suicide: What Are They, How Do They Differ, and Why Does It Matter?

Abstract: Research investigating suicide attempts and deaths by suicide has yielded many specific risk factors and warning signs for future suicidal behaviors. Yet, even though these variables are each valuable for suicide prevention efforts, they may be limited in their applicability to clinical practice. The differences among risk factors, warning signs, and "drivers," which are person-specific variables that lead individuals to desire death by suicide, are highlighted. The scarce evidence on drivers is described and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
38
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 42 publications
2
38
0
Order By: Relevance
“…For Veterans, common risk factors tend to mirror those of the civilian population, including depression (Desai, Dausey, & Rosenheck, ; Zivin et al., ), anxiety (Rudd, Goulding, & Bryan, ), posttraumatic stress disorder (PTSD; Jakupcak et al., ), sleep problems (Ribeiro et al., ), substance use (Poindexter et al., ), and alcohol use (Kim et al., ), yet the research literature reflects a more nuanced conceptualization of understanding why people are drawn toward death and dying as a means of coping with personal suffering (Tucker, Crowley, Davidson, & Gutierrez, ). Unfortunately, many clinicians continue to organize care of patients around their identified risk factors.…”
Section: Conceptualizing Suicidal Ideationmentioning
confidence: 99%
“…For Veterans, common risk factors tend to mirror those of the civilian population, including depression (Desai, Dausey, & Rosenheck, ; Zivin et al., ), anxiety (Rudd, Goulding, & Bryan, ), posttraumatic stress disorder (PTSD; Jakupcak et al., ), sleep problems (Ribeiro et al., ), substance use (Poindexter et al., ), and alcohol use (Kim et al., ), yet the research literature reflects a more nuanced conceptualization of understanding why people are drawn toward death and dying as a means of coping with personal suffering (Tucker, Crowley, Davidson, & Gutierrez, ). Unfortunately, many clinicians continue to organize care of patients around their identified risk factors.…”
Section: Conceptualizing Suicidal Ideationmentioning
confidence: 99%
“…For one, research has typically looked at individual risk factors in isolation rather than in interaction with one another (Nock et al., ; O'Connor, ). Secondly, risk assessment has often been inadequately time‐sensitive, such that most identified suicide risk factors are predictive of chronic rather than acute risk (Large, Sharma, Cannon, Ryan, & Nielssen, ; Oquendo, Currier, & Mann, ; Tucker, Crowley, Davidson, & Gutierrez, ). Hence, the goal of the current research was to develop and test a comprehensive, integrated, and time‐sensitive model of the psychological progression to suicidal behavior over time.…”
mentioning
confidence: 99%
“…Similarly, Tucker et al. () distinguish between risk factors and drivers, the former representing long‐term vulnerabilities for suicide and the latter representing immediate precipitating causes. In the Interpersonal‐Psychological Theory of Suicidal Behavior (IPT; Van Orden, Witte, Cukrowicz, Braithwaite, Selby, & Joiner, ), feelings of thwarted belongingness and perceived burdensomeness underlie suicide ideation while suicidal action is typically dependent upon acquired capability.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The CDC (2007) reported that there are approximately 100 to 200 attempts for every completed suicide. Suicide does not happen without any warning signs (Tucker, Crowley, Davidson, & Gutierrez, 2015) and suicidal patients seek medical attention months before the suicide attempt happens (Tran et al, 2014).…”
Section: Purposementioning
confidence: 99%